The emerging role of disease-associated microglia in Parkinson’s disease - Samant, Ritika R.; Standaert, David G.; Harms, Ashley S. (Frontiers in Cellular Neuroscience, 2024)
Disease-associated microglia (DAM) are a subset of microglia that appear at various stages of central nervous system neurodegenerative diseases. DAM were identified using single-cell RNA sequencing within Alzheimer's Disease (AD) where they were characterized by their unique localization near amyloid-β plaques and their phagocytic and lipid-metabolizing features. Unfortunately, activation and etiology of DAM are only understood within the context of AD where Triggering Receptor Expressed On Myeloid Cells 2 (TREM2), a receptor for amyloid-β, appears to be the key regulator in microglial transition to a DAM state. Despite this reliance on TREM2 in AD, DAM appear across other neurodegenerative diseases in which TREM2 may not be a critical player. This begs the question of if DAM are truly the same across all neurodegenerative diseases or if there exists a heterogeneity to DAM across neurodegenerative pathologies. Investigation into this critical gap in the field regarding DAM etiology and activation, as well as DAM function, could be delineated utilizing models of Parkinson's disease (PD) to complement studies in models of AD. Though highly underexplored regarding DAM, PD with its pattern of protein aggregation-associated pathology like AD could serve as the spatiotemporal comparison against AD findings to ascertain the nature of DAM. The experimental vehicle that could guide the future of such investigation is the multi-omics model. With a compound approach focusing on exploring triggers for DAM at the chromatin or mRNA level and related protein output, it becomes possible to strongly characterize and firmly answer the question of what is a DAM.